Old but gold: the role of drug combinations in improving response to immune check-point inhibitors in thoracic malignancies beyond NSCLC - Luca Cantini; Federica Pecci; Filippo Merloni; Andrea Lanese; Edoardo Lenci; Francesco Paoloni; Joachim G.J.V. Aerts; Rossana Berardi (Open Exploration Publishing Inc., 2021)
The introduction of immune checkpoint inhibitors (ICIs) in non-oncogene addicted non-small cell lung cancer (NSCLC) has revolutionized the treatment scenario and led to a meaningful improvement in patient prognosis. Disappointingly, the success of ICI therapy in NSCLC has not been fully replicated in other thoracic malignancies as small cell lung cancer (SCLC), malignant pleural mesothelioma (MPM), and thymic epithelial tumors (TETs), due to the peculiar biological features of these disease and to the difficulties in the conduction of well-designed, biomarker-driven clinical trials. Therefore, combination strategies of ICIs plus conventional therapies (either chemotherapy, alternative ICIs or targeted agents) have been implemented. Although first approvals of ICI therapy have been recently granted in SCLC and MPM (in combination with chemotherapy and different ICIs), results remain somewhat modest and limited to a small proportion of patients. This work reviews the trial results of ICI therapy in mesothelioma, SCLC, and TETs and discusses the potential of combining ICIs with old drugs.